Pengaruh Literasi Manajemen Bisnis Syariah terhadap Minat Investasi pada Pasar Modal - Dina Fakhira; Adinda Khairunisa Ahmadi; Nabila Intan Safira; Muhammad Gifari Sitorus; Pani Akhiruddin Siregar (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The main goal of this research is to examine how interest in investing in the Sharia market is influenced by Islamic financial knowledge. A thorough grasp of financial concepts that adhere to Islamic law, such as riba, zakat, and the idea of fairness in financial transactions, is necessary for Islamic financial literacy. Islamic financial literacy may have a significant role in investing choices, as shown by the rising knowledge of halal and Sharia-compliant assets. 200 respondents—both current and potential investors in the Sharia capital market—were given questionnaires as part of this study's quantitative methodology. Higher interest in investing in Sharia capital market products like sukuk and Sharia mutual funds is positively correlated with higher levels of Islamic financial literacy, according to the study's findings. These results underline the need of more comprehensive Islamic financial education initiatives to raise public awareness and aid in the growth of Indonesia's Sharia capital market. In order to stimulate investment interest, it is also determined that improvements in Sharia investment products and supporting regulations are essential. Thus, this research comes to the conclusion that promoting a more inclusive Islamic economy and developing the Sharia capital market may both be greatly aided by increasing Islamic financial literacy. This study shows that interest in investing in the Sharia capital market is strongly influenced by Islamic financial knowledge. Sharia-compliant investment products like sukuk (Islamic bonds) and Sharia mutual funds are more likely to be chosen by investors who have a firm grasp of Islamic financial concepts like riba (usury), zakat (almsgiving), and profit-sharing. The research emphasizes the value of thorough financial education initiatives and easily available information in raising public awareness of Islamic finance. It is anticipated that these initiatives would boost more inclusive and sustainable economic development in Indonesia and raise participation in the Sharia capital market.